Dehiscences and fenestrations: methodological care necessary to avoid errors in diagnosis and measurement - Alberto Consolaro
ABSTRACT The low prevalence of gingival recessions observed in orthodontic clinical practice may be assigned to the fact that in studies in which dehiscences and bone fenestrations are described as frequent, they were diagnosed based on: 1) dry skull studies; 2) areas with periosteal reflection together with flap; and 3) imaging techniques with low sensitivity to detect these defects, which have a delicate structure and function. In areas of pseudo-dehiscences and fenestrations, the periosteum and the alveolar cortical bone are very thin; also, they either have been removed during preparation of the dry specimens in the areas for analysis, or, alternatively, have not been investigated using an ideal imaging method.